Analysis of the Implementation of the Agreement on the System and Procedure for the Application of Pawn Products at PT. UPS Sibuhuan Sharia Pawnshop - M. Hizbullah Hasibuan; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
Shari'ah pawnshops run on two sharia transaction contracts, namely a rahn (pawning) contract to obtain the desired loan amount and an ijarah (lease) contract to pay the pawnshop employees for maintaining, caring for and storing the goods that are deposited because the pawnshop is an institution. a business whose orientation is profit oriented or also looking for profit. This research is qualitative, in which the research has procedures to produce descriptive data in the form of data packaged from the speaker's sentences in writing or orally regarding the behavior of the object being observed. This method uses a descriptive analysis approach which is closely related to the subject matter, namely the optimization of contracts in the system and procedures for the application of pawn products at PT. Pegadaian UPS Sibuhuan. Then, the results of the analysis found that the system and procedure for the application of pawn products with sharia transaction contracts were optimal and appropriate, so that good pawn transactions were established between the company and customers which aimed at creating good cooperation between the two.